Development Of Computer Based Test Online Standard Arabic Language (ILAA)/ Pengembangan Aplikasi Computer Based Test Online Bahasa Arab Terstandar (ILAA) - Hamid, M Abdul; Charis, M Abdullah (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
This research aims 1) the realization of a practical application system for Computer Based Test Online for Standard Arabic Language (ILAA). 2) Describing the feasibility of the ILAA. The research and development model used is the ADDIE (Analysis-Design-Development-Implementation-Evaluation) model developed by Reiser and Mollenda in 1990. This model was chosen because when used in the development, this process is considered sequential and interactive. The evaluation of each stage can bring development to the previous stage. The result of one stage is the initial product for the next stage. The Language Development Center of UIN Maulana Malik Ibrahim Malang, Indonesia as the subject and data collection techniques using structured interviews, documentation, and questionnaires. The collected data were analyzed using the percentage formula. The results: 1) Development of the Online CBT Application for Arabic Language Test (ILAA) using MOODLE (Modular Object-Oriented Dynamic Learning Environment). The ILAA Arabic language test CBT application can be accessed through www.tesbahasa.uin-malang.ac.id. 2) Based on expert and student assessments; The Arabic language test online CBT application (ILAA) at the Language Development Center of UIN Maulana Malik Ibrahim Malang is perfect and easy to use. This is evidenced by 93% of respondents choosing very good, easy, clear, and precise. Only 4.8% chose very poor and poor, less accessible and less precise answers.